Serving consumers in an uncertain world: A credence goods experiment - Loukas Balafoutas; Helena Fornwagner; Rudolf Kerschbamer; Matthias Sutter; Maryna Tverdostup (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2023)
Credence goods markets are prone to fraudulent behavior and market inefficiencies due to informational asymmetries between sellers and customers. We examine experimentally the effects of diagnostic uncertainty and insurance coverage on the information acquisition and provision decisions by sellers and the trading decisions by consumers. Our results reveal that diagnostic uncertainty is a major source of inefficiency by decreasing efficient service provision. Insurance coverage has a positive net effect on market efficiency, despite making information acquisition and efficient service provision less likely. We also examine the role of -s and of sellers' prosociality in shaping service provision and information acquisition.
Keywords: C91; D82; G22; 330; Credence goods; diagnostic uncertainty; insurance coverage; experiment